The Role of Cognition, Personality, and Trust in Fraud Victimization in Older Adults - Judges, Rebecca A.; Gallant, Sara N.; Yang, Lixia; Lee, Kang (Frontiers in Psychology, 2017)
Older adults are more at risk to become a victim of consumer fraud than any other type of crime (Carcach, Graycar, & Muscat, 2001) but the research on the psychological profiles of senior fraud victims is lacking. To bridge this significant gap, we examined 151 (120 female, 111 Caucasian) community-dwelling older adults in Southern Ontario between 60 and 90 years of age about their experiences with fraud. Participants had not been diagnosed with cognitive impairment or a neurological disorder by their doctor and looked after their own finances. We assessed their self-reported cognitive abilities using the MAQ, personality on the 60-item HEXACO Personality Inventory, and trust tendencies using a scale from the World Values Survey. There were no demographic differences between victims and non-victims. We found that victims exhibit lower levels of cognitive ability, lower honesty-humility, and lower conscientiousness than non-victims. Victims and non-victims did not differ in reported levels of interpersonal trust. Subsequent regression analyses showed that cognition is an important component in victimization over and above other social factors. The present findings suggest that fraud prevention programs should focus on improving adults’ overall cognitive functioning. Further investigation is needed to understand how age-related cognitive changes affect vulnerability to fraud and which cognitive processes are most important for preventing fraud victimization.